(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Particulate matter (PM) was identified as the main air pollutants in Malaysia which directly impose a treat to human health and understanding this pollutant is also crucial for its mitigation and control. This study aims to determine and characterize the PM2.5 with the influence of meteorological parameters. The PM2.5 samples were collected at Perai, Nibong Tebal and highway of Penang Bridge represented the industrial, residential, and roadside areas of Mainland Penang, respectively. The descriptive statistical analysis was conducted to understand the variations of PM2.5 concentration on the study areas, while its relationship with meteorological parameters were tested using Pearson correlation. Eleven heavy metals and three anions were determined using mass spectrometry (ICP-MS) and Ion Chromatography, respectively. Results showed that the mean concentration of PM2.5 are 10.88 ?g/m³, 31.96 ?g/m³, and 39.35 g/m³ for residential area, industrial area, and roadside, respectively. The results revealed that mean concentrations of PM2.5 (39.35 ?g/m³) in the roadside are significantly higher than NAAQG 24-h average of 35 ?g/m³. Result also suggested that meteorological parameters were lest significant in controlling the PM2.5 concentrations as only the air pressure was found to be significant with the value of correlation coefficient of 0.476. The major components such as SO42-, K and Na account for about 70-90% of the PM2.5.